2017
DOI: 10.7150/jca.17858
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Patterns of Regional Failure for Nasopharyngeal Carcinoma following Intensity-Modulated Radiation Therapy

Abstract: Purpose: To analyze the long-term patterns of regional failure following intensity-modulated radiotherapy (IMRT) for nasopharyngeal carcinoma (NPC).Methods: From January 2005 to December 2010, 275 non-metastatic NPC patients treated with IMRT were retrospectively enrolled. Patients staged as II (lymph nodes measuring 4 or more cm in diameter), III or IV also received chemotherapy. Failures were assessed as in-field or out-field relative to the pretreatment planning computed tomography data sets. Univariate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 30 publications
2
19
2
Order By: Relevance
“…For all patients, the estimated 5-year OS, LRFS, DMFS and DFS rates were 87.5%, 94.1%, 87.0%, and 81.5%, respectively. The survival of our cohort was relatively better than those in other studies of 5-year overall survival rate varying from 83.9 to 87.4% in all-stages NPC patients treated with IMRT [ 19 , 29 31 ]. The relatively short follow-up time (median: 58 months) in our study may lead to the higher survival rate.…”
Section: Discussioncontrasting
confidence: 65%
“…For all patients, the estimated 5-year OS, LRFS, DMFS and DFS rates were 87.5%, 94.1%, 87.0%, and 81.5%, respectively. The survival of our cohort was relatively better than those in other studies of 5-year overall survival rate varying from 83.9 to 87.4% in all-stages NPC patients treated with IMRT [ 19 , 29 31 ]. The relatively short follow-up time (median: 58 months) in our study may lead to the higher survival rate.…”
Section: Discussioncontrasting
confidence: 65%
“…The T and N stages are associated with LRFS and DMFS, as demonstrated by previous research. [ 28 , 29 ] Xu et al demonstrated that IC plus CCRT has no significant survival benefit for patients with locoregionally advanced NPC but results in significant metastasis-free survival efficacy in T3 to 4/N0 to 1 populations. [ 30 ] However, more and more hard evidence has confirmed that a combination of IC and CCRT is a promising treatment strategy for NPC.…”
Section: Discussionmentioning
confidence: 99%
“…Regional relapse is one of the main failure patterns for NPC patients treated with IMRT 15 , 16 . The correct diagnosis, accurate delineation of metastatic CLNs, and radical radiation of such nodes are extremely important for the success of radiotherapy, especially when using IMRT.…”
Section: Discussionmentioning
confidence: 99%